Aspergillus sydowii strain scau066 and aspergillus versicolor isolate bab-6580: potential source of xylanolytic, cellulolytic and amylolytic enzymes / Nur Syahira Mohammad and Zaidah Zainal Ariffin - Mohammad, Nur Syahira; Ariffin, Zaidah Zainal (Faculty of Applied Sciences, 2020)
Fungi is known to produce a wide range of biologically active metabolites and enzymes. Enzymes produced by fungi are utilized in food and pharmaceutical industries because of their rich enzymatic profile. Filamentous fungi are particularly interesting due to their high production of extracellular enzymes which has a large industrial potential. The aim of this study is to isolate potential soil fungi species that are able to produce functional enzymes for industries. Five Aspergillus species were successfully isolated from antibiotic overexposed soil (GPS coordinate of N3.093219 E101.40269) by standard microbiological method. The isolated fungi were identified via morphological observations and molecular tools; polymerase chain reactions, ITS 1 (5'- TCC GTA GGT GAA CCT GCG G3') forward primer and ITS 4 (5'-TCC TCC GCT TAT TGA TAT GC-3') reverse primer. The isolated fungi were identified as Aspergillus sydowii strain SCAU066, Aspergillus tamarii isolate TN-7, Aspergillus candidus strain KUFA 0062, Aspergillus versicolor isolate BAB-6580, and Aspergillus protuberus strain KAS 6024. Supernatant obtained via submerged fermentation of the isolated fungi in potato dextrose broth (PDB) and extracted via centrifugation was loaded onto specific media to screen for the production of xylanolytic, cellulolytic and amylolytic enzymes. The present findings indicate that Aspergillus sydowii strain SCAU066 and Aspergillus versicolor isolate BAB-6580 have great potential as an alternative source of xylanolytic, cellulolytic and amylolytic enzymes.